Is There a Limitation of RECIST Criteria in Prediction of Pathological Response, in Head and Neck Cancers, to Postinduction Chemotherapy?. (11th September 2013) - Patil, V.; Noronha, V.; Joshi, A.; Muddu Krishna, Vamshi; Juvekar, S.; Pantvaidya, Gauri; Chaturvedi, Pankaj; Chaukar, D.; Arya, Supreeta; Patil, Aswari; Bhosale, B.; Dongre, A.; et al.
Abstract : This study studied the coorelation between radiological response to induction chemotherapy and acheivement of pCR or near pCR. It was a retrospective analysis in which all patients who received NACT from 2008 till april 2012 were subjected to inclusion criteria. Coorelation analysis was performed between CR + PR and acheivement of pCR or near pCR. Twenty four patients were identified.The primary site of tumor was oral cavity in 19 patients (79.2%), maxilla in 2 patients (4.2%), laryngopharynx in 2 patients (4.2%) and oropharynx in 1 patient (4.2%). The clinical stage was stage IVA in 16 patients ( 66.7%) and IVB in 8 patients (33.3%). The overall response rates ie a combination of CR and PR was seen in 11patients (45.8%). The pCR was seen in 15 patients (62.5%) and rest had near pCR. There was no linear coorelation between radiological size decrement and tumor response. On coorelation analysis the spearman correlation coefficent was −0.039 (P = 0.857 ). This suggest that presently used radiological response criterias for response assesment in head and neck cancers severly limit our ability to identify patients who would have pCR or near pCR.